Impact of corona virus on fishermen's business in Labuan Bajo - Ariani, Zaenafi; Sinta, Nur; arti, Juni; Maulana, Bayu (Journal of Sharia Economy and Islamic Tourism, 2021)
Abstract: The World Health Organization (WHO) explains that this corona virus is an infectious disease that attacks the human respiratory system. The corona virus causes the common cold to the point where it can cause death. The origin of this virus originated from Wuhan China, then spread throughout the world including Indonesia. In West Manggarai Regency, precisely in Labuan Bajo Village, a lockdown is implemented for 14 days, everyone is prohibited from going out of the house, including business/trade/entertainment/school activities or activities in Komodo Island Village, whose profession is relatively a fisherman. With this lockdown, fishermen are confused when making a living, because expenses keep coming out while there is no income. Abstrak: World Health Organization (WHO) menjelaskan bahwa corona virus ini merupakan penyakit menular yang menyerang sistem pernapasan manusia. Virus corona menyebabkan penyakit flu biasa sampai bisa menyebabkan kematian. Asal mula virus ini berawal dari Wuhan China, lalu menyebar ke seluruh dunia termasuk Indonesia. Di Kabupaten Manggarai Barat, tepatnya di Desa Labuan Bajo menerapkan lockdown selama 14 Hari, setiap orang dilarang beraktivitas keluar rumah, termasuk aktivitas Usaha/ dagang/hiburan/ sekolah ataupun aktivitas di Desa Pulau Komodo yang relatif profesinya sebagai Nelayan. Dengan adanya lockdown ini para nelayan kebingungan saat mencari nafkah, soalnya pengeluaran tetap keluar sedangkan pemasukan tidak ada.